Побудова трирівневого механізму формування інноваційного потенціалу промислового підприємства - Попель, С. А.; Popel, Sergey (КНТУ, 2015)
В статті обґрунтовано основні завдання механізму формування інноваційного потенціалу промислового підприємства. Запропоновано трирівневу структуру механізму і розглянуто кожен із виділених рівнів. Наведена характеристика основних елементів механізму формування інноваційного потенціалу підприємства. Запропоновано методику аналізу стану інноваційного потенціалу та алгоритм оцінювання якості й прогнозування майбутнього рівня інноваційного потенціалу. The purpose of the article is to build three-tier mechanism of formation of innovative potential of industrial enterprises and research of its main elements. The main objectives of the mechanism of formation of innovative potential of industrial enterprises were justified in the article. Three-tier structure of the mechanism was proposed by the author and every of the selected levels were examined. The characteristic of the main elements of the mechanism of formation of innovative potential of the company was represented. The method of analysis of the innovation potential and quality assessment algorithm and prediction of future innovation potential were offered in the study. The proposed three-level mechanism of innovative potential of industrial enterprises allows it to quickly responding and appropriately responding to changing external economic environment.
Construction of Three-Tier Mechanism of Formation of Innovative Potential of Industrial Enterprises
Keywords: інноваційний потенціал; механізм формування інноваційного потенціалу; оцінювання і прогнозування інноваційного потенціалу; innovative potential; mechanism of formation of innovative potential; assessment and forecasting of innovation potential